2013
DOI: 10.4103/0970-9290.117993
|View full text |Cite
|
Sign up to set email alerts
|

A new technique to determine vertical dimension of occlusion from anthropometric measurements of fingers

Abstract: Since the variations between VDO and finger lengths are within the range of 2-4 mm, VDO prediction through this method is reliable, and reproducible. Also the method is simple, economic, and non-invasive; hence, it could be recommended for everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
49
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 0 publications
8
49
1
15
Order By: Relevance
“…Therefore, in order to evaluate the OVD, a pluralistic method should be adopted at all the stages of rehabilitation in order to maximize the benefits and minimize damage to the stomatognathic system. 18 The results obtained in this research support almost all the hypothesis, hence the length of pupil-rima oris can be suggested to be used as one of the guide in the determination of OVD. However, other method of determination of OVD should be used together in order to obtain a more accurate measurement.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Therefore, in order to evaluate the OVD, a pluralistic method should be adopted at all the stages of rehabilitation in order to maximize the benefits and minimize damage to the stomatognathic system. 18 The results obtained in this research support almost all the hypothesis, hence the length of pupil-rima oris can be suggested to be used as one of the guide in the determination of OVD. However, other method of determination of OVD should be used together in order to obtain a more accurate measurement.…”
supporting
confidence: 73%
“…Also, it does not require a great amount of time and experience to master which is another advantage over previous methods. 18 Besides the pupil-rima oris, there are many other methods in previous studies which is using the anthropometric landmarks to compare with the OVD. Anthropometric measurements were used in order to determine proportions of body parts since antiquity, when sculptors and mathematicians followed the golden proportions, later specified as a ratio of 1.618:1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations